Women and discrimination in Universities: brief description of their organizations on a global scale. A reflection of an investigation in the UNLu (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
This is a brief historical journey on women's organizations that work with the problem of discrimination within the academic world in Universities in the world, in Latin America and in Argentina, with emphasis on female segregation practices but also on those of inclusion, which have recently been promoted within governance as practices for their vindication.Finally, there will be a reflection on a research project carried out at the UNLu that addressed the topic: Paid and unpaid work: Towards measuring the use of time in UNLu teachers, presented and approved between 2013 and 2014.
Keywords: women; University Organizations; Use of time; Teachers UNLu